2015
DOI: 10.3389/fpls.2015.00664
|View full text |Cite
|
Sign up to set email alerts
|

An engineered lipid remodeling system using a galactolipid synthase promoter during phosphate starvation enhances oil accumulation in plants

Abstract: Inorganic phosphate (Pi) depletion is a serious problem for plant growth. Membrane lipid remodeling is a defense mechanism that plants use to survive Pi-depleted conditions. During Pi starvation, phospholipids are degraded to supply Pi for other essential biological processes, whereas galactolipid synthesis in plastids is up-regulated via the transcriptional activation of monogalactosyldiacylglycerol synthase 3 (MGD3). Thus, the produced galactolipids are transferred to extraplastidial membranes to substitute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 59 publications
0
16
0
Order By: Relevance
“…In the present study, LP stress decreased net photosynthetic rate, which was attributed to reduced stomatal conductance in tomato leaves (Table 2). Notably, P deficit conditions lead to breakdown of phospholipids in the chloroplast membranes to release Pi, which could be a potential reason for reduced photosynthetic rate [42]. In addition, enhanced carbohydrate (starch and sugars) accumulation in chloroplasts under Pi-depleted conditions may also result in attenuated photosynthetic activity [42,43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, LP stress decreased net photosynthetic rate, which was attributed to reduced stomatal conductance in tomato leaves (Table 2). Notably, P deficit conditions lead to breakdown of phospholipids in the chloroplast membranes to release Pi, which could be a potential reason for reduced photosynthetic rate [42]. In addition, enhanced carbohydrate (starch and sugars) accumulation in chloroplasts under Pi-depleted conditions may also result in attenuated photosynthetic activity [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, P deficit conditions lead to breakdown of phospholipids in the chloroplast membranes to release Pi, which could be a potential reason for reduced photosynthetic rate [42]. In addition, enhanced carbohydrate (starch and sugars) accumulation in chloroplasts under Pi-depleted conditions may also result in attenuated photosynthetic activity [42,43]. However, exogenous Si application significantly increased photosynthetic pigment contents as well as net photosynthetic rate under LP stress compared with that under LP stress alone.…”
Section: Discussionmentioning
confidence: 99%
“…Lipid droplets have a well-known function in energy storage but proteomic analyses of plant LDs showed that they might also play alternative roles, particularly during stress (Pyc et al, 2017; Yang and Benning, 2018). TAG accumulation was observed during nitrogen or Pi deprivation in higher plants (Gaude et al, 2007; Pant et al, 2015; Shimojima et al, 2015; Mei et al, 2017), and such increases were also significantly enhanced in the presence of sugar (Yang et al, 2011). In A. thaliana cell cultures, TAG accumulation seems to be a frequent response to cell growth arrest mediated by nutrient stresses or chemical drugs, such as MTX (Mei et al, 2017).…”
Section: Lipid Trafficking Under Stress Conditionmentioning
confidence: 98%
“…These observations are at the basis of numerous strategies to produce third generation biofuels. These effects have been less studied in higher plants, but it was observed in Arabidopsis seedlings that the amount of TAG increased during nitrogen deprivation (Gaude et al, 2007; Shimojima et al, 2015), and that such increase was also significantly enhanced in the presence of sugar (Yang et al, 2011). The reasons why nutrient deficiencies induce TAG accumulation are not clear.…”
Section: Introductionmentioning
confidence: 99%